A STUDY ON TEACHING LISTENING SKILL AT SD NEGERI 2 BATURETNO WONOGIRI - YANOARTI , NURIANA (2007)
The research studies about the teaching listening skill at SD N 2 BATURETNO WONOGIRI. The object of research is the implementation of teaching listening which is conducted in SD Negeri 2 Baturetno Wonogiri especially at fifth year. The research belong to descriptive qualitative research. The objective of research is to describes the implementation of teaching listening skill in SD Negeri 2 Baturetno Wonogiri. It covers the method of teaching listening, the problems faced by teacher in teaching listening, and the problems of students in learning listening. To achieve those objectives the writer collects the data by observation, interview, and documentation. Based on the result and data analysis the writer finds that the method of teaching listening is using communicative language teaching. It can be observed from the student's activity in the classroom. The students are enough active. Meanwhile, the problems faced teachers are about the time and classroom management. The problems faced by students are limited vocabularies, the pronunciation, the speed of native speaker's sound, and the difficulty to concentrate. In teaching learning process, sometimes the English teacher takes the score of students to evaluate the result of teaching learning process.